The Roles of Basic Education Commission Affecting the Competencies of Learners in Schools Under Krabi Primary Educational Service Area Office - Patitang, Yanin; Sumato, Phramaha Supot; Phra Kru Phichitsuphakan; Kulkham, KhemJira (Academic MCU Buriram Journal, 2021)
This research aimed 1) to study the roles of primary school board, 2) to study the major competencies of learners, and3) to present the guidelines and recommendations on The roles of basic education commission affecting the competencies of learners in schools under Krabi primary educational service area office. The quantitative was designed for this research. The sample composed of 351 school administrators, teachers and five of key informants, The instrument for data collection was a set of questionnaires The reliabe value was wat 0.98. The data were analyzed by frequency, percentage, average mean, standard deviation, t-test and One-Way ANOVA. The research result finds that: 1. The roles of basic education commission affecting to major competencies of learners by overview is at the highest level when considering in each aspect It is found that the aspect of approving the curriculum focused on the needs of local is the highest mean, the lowest mean is the aspect of encouraging all children in the service area to receive a primary as coverage and standardization respectively. 2. The results of analysis of data on the major competencies of by overview is at a high level. When considering in each aspect, it is found that the aspect with the highest mean is the ability in communication, followed by the ability to use life skills. As for the ability to solve problems with the lowest average 3. The forecast variables in six aspects i.e. 83.50 %, and other variables are not effected. the suggestion the guideline on the roles of basic education commission on major competencies of learners must be analysis on internal factor sand external factors, survey the expectation, opportunity and obstacles from the participation, to formulate the clear goals, to find out the scholarship, materials and the needs for learners who are lacking, to enhance for protecting the children’s rights, kidnaper caring, disadvantage, and talent children to get the competency development, to enhance and support learner in any school to get the development in each person as much as possible.